Asymmetric synthesis of Ru(II)-dialkyl-pheox catalysts from (S)-2-Amino-phenylehanol for cyclopropanation - Lê, Thị Loan Chi; Iwasa, Seiji (Hue University Journal of Science: Natural Science, 2023)
The development of new pharmaceutical products containing pure enantiomers is a recent direction in the world’s pharmaceutical industry. Asymmetric catalysts play an essential role in the synthesis of pure enantiomers. The Ru(II)-pheox catalyst has been reported to be effective for the asymmetric reactions producing pure enantiomers. In this study, an asymmetric synthesis of Ru(II)-dialkyl-pheox derivatives is proposed. The process consists of the asymmetric synthesis of oxazoline derivatives from precursors and the complexation between ruthenium and oxazoline ligands. With this procedure, four Ru(II)-dialkyl-pheox derivatives were successfully synthesized with a high yield (>60%).